Review on Antifungal Resistance Mechanisms in the Emerging Pathogen Candida auris - Chaabane, Farid; Graf, Artan; Jequier, Léonard; Coste, Alix T. (Frontiers in Microbiology, 2019)
Candida auris is an emerging multi-drug resistant yeast, that causes major issues regarding patient treatment and surface disinfection in hospitals. Indeed, an important proportion of C. auris strains isolated worldwide present a decreased sensitivity to multiple and sometimes even all available antifungals. Based on recent tentative breakpoints by the CDC, it appears that in the USA about 90, 30 and less than 5 percent of isolates have been resistant to fluconazole, amphotericin B and echinocandins, respectively. To date, this has lead to a low therapeutic success. Furthermore, C. auris is prone to cause outbreaks, especially since it can persist for weeks in a nosocomial environment and survive high-end disinfection procedures. In this review, we describe the molecular resistance mechanisms to antifungal drugs identified so far in C. auris and compare them to those previously discovered in other Candida species. Additionally, we examine the role that biofilm formation plays in the reduced antifungal sensitivity of this organism. Finally, we summarise the few insights on how this yeast survives on hospital surfaces and discuss the challenge it presents regarding nosocomial environment disinfection.